Measurement of Website Service Quality Using Webqual 4.0 (Case Study of Kotakaler Village Website) - Leni Nurhayati; Sri Bekti Handayani Ningsih (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2020)
The need for accurate, fast, current, relevant and reliable information for the community is a necessity in the information age. In order to meet these needs and encourage good governance with the support of information and communication technology, local government websites have been built. Local government websites that can provide a variety of information and services are expected to support the creation of smart citizens and smart government. Government website is not enough just to be built but its quality must also be evaluated. This study measures the quality of the local government website (case study of Kotakaler Village) so that the level of quality can be known to provide an overview or reference in developing the website itself. This research is a qualitative descriptive study. Website quality assessment using the WebQual method which is a method of measuring website quality based on end-user perception in three dimensions, consisted of information quality, interaction quality, and usability. The results showed that the website of the boxer village has a high level of quality in all three dimensions. Keywords: Website, WebQual, Usability, Information Quality, Interaction Service Quality